National Poets, the Status of the Epic and the Strange Case of Master William Shakespeare - Innes, Paul (Multicultural Shakespeare: Translation, Appropriation and Performance, 2016)
This essay contextualises Shakespeare as product of a field of forces encapsulating national identity and relative cultural status. It begins by historicising the production of national poets in Romantic and Nationalist terms. Lefevere’s conceptual grid is then used to characterise the system that underpins the production of Shakespeare as British national poet, and his place within the canon of world literature. The article defines this context first before moving onto the figure of Shakespeare, by referring to various high status texts such as the Kalevala, the Aeneid, The Faerie Queene and Paradise Lost. The position accorded Shakespeare at the apex is therefore contingent upon a series of prior operations on other texts, and their writers. Shakespeare is not conceived as attaining pre-eminence because of his own innate literary qualities. Rather, a process of elimination occurs by which the common ascription of the position of national poet to a writer of epic is shown to be a cultural impossibility for the British. Instead, via Aristotle’s privileging of tragedy over epic, the rise of Shakespeare is seen as almost a second choice because of the inappropriateness of Spenser and Milton for the position.